Discrimination of gender-, speed-, and shoe-dependent movement patterns in runners using full-body kinematics - Maurer, C.; Federolf, P.; von Tscharner, V.; Stirling, L.; Nigg, B. M. (Gait and Posture, 2012)
Changes in gait kinematics have often been analyzed using pattern recognition methods such as principal component analysis (PCA). It is usually just the first few principal components that are analyzed, because they describe the main variability within a dataset and thus represent the main movement patterns. However, while subtle changes in gait pattern (for instance, due to different footwear) may not change main movement patterns, they may affect movements represented by higher principal components.